EXPLORING THE USE OF THE “L-BY-D FRAMEWORK OF MULTILITERACIES PEDAGOGY” IN A UNIVERSITY CONTEXT - Untari Gunta Pertiwi; Afri Wita; Nia Kurniawati (Jurnal Ilmiah Bina Bahasa, 2026)
Learning-by-Design (L-by-D) is derived from Multiliteracies pedagogy and responds to the evolution of learning, particularly in the literacy field, from traditional to multiliteracies, driven by technological advancement. The pedagogy proposes an active learning approach that empowers teachers as learning designers and students through the four knowledge processes: Experiencing, Conceptualizing, Analyzing, and Applying. These knowledge processes make it possible to apply L-by-D in both language and literacy teaching. The study intends to explore the implementation of the “L-by-D Framework” in the Collaborative Presentation Course for 40 engineering students and the students’ perceptions of the implementation. The study uses a qualitative approach with a case study design, employing questionnaires, classroom observations, and learning artifacts. The results demonstrate that the L-by-D Framework can be implemented in the Collaborative Presentation Course with the teacher’s intervention. It provides a comprehensive learning process for students to learn presentation theory, including how to deliver presentations. This design assists students in being active agents of learning by helping them learn how to know. The implementation also gains positive perceptions from the students. Further research should explore flexible and mixed designs, as the study focuses solely on the sequential design.